Internalisasi Nilai-Nilai Karakter Religius Melalui Pembelajaran Pendidikan Agama Kristen di SD Inpres Lili - Yakobus Adi Saingo (APOSTOLOS, 2023)
The purpose of this study was to determine the internalization of religious character values ??through learning Christian Religious Education at SD Inpres Lili. This study uses a qualitative method. Data were obtained by interviewing Christian Religious Education teachers. Then the data were analyzed by reducing the data and described. The results of this study indicate the internalization of religious character values ??through the learning of Christian Religious Education at SD Inpres Lili which is based on the dimensions of Glock and Stark religiosity, namely: belief/faith (religious belief), religious practice (religious practice), appreciation (religious feeling) , knowledge (religious knowledge), practice (religious effect). Religious character values ??that are internalized through learning Christian Religious Education include an attitude of faith in Jesus Christ as God, carrying out a series of worship in daily life, always being grateful and making religion a way of life, practicing religious teachings to help others, willing to work together, and forgive each other when there is a dispute. The internalization of religious character values ??based on Glock and Stark's religiosity dimension theory, through the study of Christian Religious Education at Inpres Lili Elementary School, turned out to be quite effective because each has a relationship with one another.